1981
DOI: 10.1029/jc086ic07p06643
|View full text |Cite
|
Sign up to set email alerts
|

Flexural waves in the Ross Ice Shelf

Abstract: Flexural waves related to the ocean swell are identified more than 600 km from the open sea in the Ross Ice Shelf, Antarctica, where the ice cover is in places more than 500 m thick. An equation relating the power spectra of the flexural wave and the ocean swell is derived, based on the continuity of pressure in the fluid layer across the ice front. Correcting for the effect of the ice, the power spectrum of the wave in the ice compares to that of the ocean swell elsewhere in the Pacific Ocean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…(Okal and MacAyeal, 2006)) and are probably excited by passing meteorological conditions and by ocean swell propagating into the Antarctic from afar (e.g. Williams and Robinson, 1981;MacAyeal and others, 2006b). The band of noise in the 0.01-0.06 Hz range is well displayed by the spectrograms of all example events shown in Figure 5a.…”
Section: Background Noisementioning
confidence: 98%
“…(Okal and MacAyeal, 2006)) and are probably excited by passing meteorological conditions and by ocean swell propagating into the Antarctic from afar (e.g. Williams and Robinson, 1981;MacAyeal and others, 2006b). The band of noise in the 0.01-0.06 Hz range is well displayed by the spectrograms of all example events shown in Figure 5a.…”
Section: Background Noisementioning
confidence: 98%
“…Tsunami‐generated peak beam power occurs at a lower frequency than the peak IG response (Figure ; black dots in Figures a and b). These results are consistent with flexural‐gravity wave theory [ Fox and Squire , ] and with prior IG wave‐generated flexural‐gravity wave measurements determined using a sparse gravimeter array on the RIS [ Williams and Robinson , ].…”
Section: Water‐ice‐coupled Flexural‐gravity Wave Propagation Charactementioning
confidence: 99%
“…The seismometer recorded a variety of signals during the field campaign [ Okal and MacAyeal , 2006] including earthquakes, tsunamis, iceberg‐generated tremor and, what is featured in the present study, sea swell incident on the ice shelf from points of origin distributed across the North and South Pacific, the Indian and the Southern oceans. In this respect, a unique aspect of this deployment is that the seismometer on the floating ice shelf responds not only to elastic waves propagating in the ice, but directly to the motion of the ice shelf as a whole, even if the ice is totally rigid (e.g., as when the ice shelf rocks and bobs, as described by Okal and MacAyeal , 2006), as well as to flexure of the ice shelf as it attempts to conform to the ocean surface on which it floats (e.g., as is the case of flexural gravity waves described by Williams and Robinson , 1981). Indeed, Okal and MacAyeal [2006] showed that this seismometer (and similar ones located on nearby drifting icebergs) recorded the 3‐D motion of the surface of the sea during the great 2004 Sumatra tsunami.…”
Section: Summary Of Ice Shelf Seismometer Signalsmentioning
confidence: 99%
“…Their research indicated that icebergs can display a resonant response to swell, however their field program was short, and only involved several days of operation. Gravimeters used to study ocean tides on the Ross Ice Shelf [ Williams and Robinson , 1981] also detected motions attributed to ocean swell with period below 100 s at a location about 600 km south of the seaward ice front where the ice shelf thickness was approximately 500 m. In both prior measurement efforts, the results came at the cost of very great logistical effort, thus making further study less appealing.…”
Section: Introductionmentioning
confidence: 99%